Domestic Use of Cooking Fuel in India: A Review on Emission Characteristics and Associated Health Concerns - Verma, Madhuri; Pervez, Shamsh; Deb, Manas Kanti; Majumdar, Dipanjali (Asian Journal of Chemistry, 2017)
One out of every three Indians use biomass fuels such as wood, animal dung and coal cake, crop residues as their primary domestic energy source. About 23 and 61 % of urban and rural Indian households, respectively, rely on traditional stoves (Chullah) for cooking practices. Household air pollution contains solid fuel burning emissions prominently, is reported to claim 4.3 million premature deaths yearly in developing countries. But most of the review studies to address air pollution scenario in India are focused on outdoor environments; major reason to review the current knowledge on emission estimates from household biomass burning and associated impacts on indoor air and human health. This review intends to critically discuss the variability associated with emission estimates and impacts of household air quality in different parts of India as presented in several research works, published during 2001-2015. About 27 and 11 % increase in PM2.5 and PM10, respectively has been observed in Indian house-indoors during the assessment period. Emission factors, emission budgets of aerosol fractions, carbonaceous matter and other chemical components for household biofuel burning emissions were also summarized for the period of 2001-2015. Health effects studies due to household air pollution in India were also summarized and discussed. Improvement in ventilation system and modification in the pattern of fuels may contribute to reduce the effect of the pollution on national health. As there are no specific regulations or acts for controlling of household air pollution in India, urgent need is felt for implementing the strategies to create public awareness.